2008
DOI: 10.1016/j.jallcom.2007.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study on planar clustering of xenon in UO2

Abstract: Interatomic potentials of uranium dioxide are investigated on their applicability to model structural stabilities beyond fluorite phase by comparing with ab-initio results. A high pressure cotunnite phase and loosely stacking virtual crystal are involved in order to get a primary confidence for large-scale deformation modelings of UO 2 under irradiation damages. The behavior of Xe atoms in UO 2 fuel is studied with molecular dynamics simulations. Besides the ground state bubble geometry, we find that a planar … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 47 publications
5
32
0
Order By: Relevance
“…Mao et al 12 considered the segregation of yttrium (Y) to symmetric Σ5 tilt GBs in cubic zirconia (ZrO 2 ) using density functional theory (DFT). Y 3+ segregation to Zr 4+ sites in the GB was predicted to be energetically favorable compared to the bulk, in agreement with the experimental results of Dickey et al 13 It is clear, therefore, that segregation of external species to GBs and dislocations may play an important role in influencing material properties. This is especially true for UO 2 where segregation may affect fission gas distribution throughout a nuclear fuel grain.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Mao et al 12 considered the segregation of yttrium (Y) to symmetric Σ5 tilt GBs in cubic zirconia (ZrO 2 ) using density functional theory (DFT). Y 3+ segregation to Zr 4+ sites in the GB was predicted to be energetically favorable compared to the bulk, in agreement with the experimental results of Dickey et al 13 It is clear, therefore, that segregation of external species to GBs and dislocations may play an important role in influencing material properties. This is especially true for UO 2 where segregation may affect fission gas distribution throughout a nuclear fuel grain.…”
supporting
confidence: 87%
“…The Xe interaction with the uranium and oxygen atoms has been fit to DFT+U energies by Geng et al 13 using a Lennard-Jones potential for Xe-Xe and Xe-O and a Born-Mayer term for the Xe-U interaction. Geng et al used this potential to examine Xe (111) planar clustering in UO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Due to its high impact on nuclear fuel performance the properties of Xe in UO 2±x have been extensively studied using a variety of theoretical 2,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] and experimental techniques [3][4][5][25][26][27][28][29][30][31] . Matzke et al [3][4][5] have published several reviews on this topic and concluded that Xe diffusion can be represented by an Arrhenius model, D = D 0 e −Ea/k b T , with activation energies (E a ) that depend on UO 2±x stoichiometry.…”
Section: Thermodynamicsmentioning
confidence: 99%
“…Using pair potential model, we studied the planar clustering of Xe aggregating in UO 2 [12] (Fig. 3).…”
Section: Computational Studymentioning
confidence: 99%